Effects of fusion height of tip winglet on the clearance flow in a compressor cascade. (December 2022) - Xu, Wenfeng; Sun, Peng; Zhong, Jingjun; Han, Shaobing; Yang, Guogang
The leakage flow generated by rotor clearance seriously affects efficiency and stability of a compressor. In order to reduce the effect of leakage flow, the tip winglet has been applied at the tip of a transonic compressor cascade. Numerical simulation has been used to investigate the influence of tip winglets with different fusion heights on the flow field structure. Furthermore, the effect of winglets was analyzed under different clearance heights and incidence angles. Results reveal that the winglet can weaken the kinetic energy of the leakage flow. The development of the leakage vortex along the pitchwise is suppressed, and the total pressure loss is decreased near the tip. The increase in the tip separation vortex scale leads to a remarkable decrease in the leakage flow rate. With the increase in fusion height, the scale of tip separation vortex decreases gradually, and the suppression effect on the leakage flow rate is weakened. The optimal scheme can reduce the loss by 3.3% and leakage flow rate by 13.4%. The suppression effect of the winglet on flow loss increases gradually with the increase in incidence angle. Moreover, the suppression effect of the winglet on leakage flow and flow loss increases first and then decreases with the increase in tip clearance.